Diversity and Philanthropy at African American Museums Black Renaissance - Banks, Patricia A. (Routledge Research in Museum Studies, 2019)
Diversity and Philanthropy at African American Museums is the first scholarly book to analyze contemporary African American museums from a multifaceted perspective. While it puts a spotlight on the issues and challenges related to racial politics that black museums collectively face in the 21st century, it also shines a light on how they intersect with corporate culture, youth culture, and the broader cultural world. Turning the lens to philanthropy in the contemporary era, Banks throws light on the establishment side of African American museums and demonstrates how this contrasts with their grassroots foundations. Drawing on over 80 in-depth interviews with trustees and other supporters of African American museums across the United States, this book offers an inside look at the world of cultural philanthropy. While patrons are bound together by being among the distinct group of cultural philanthropists who support black museums, the motivations and meanings underlying their giving depart in both subtle and considerable ways depending on race and ethnicity, profession, generation, and lifestyle. Revealing not only why black museums matter in the eyes of supporters, the book also complicates the conventional view that social class drives giving to cultural nonprofits. It also paints a vivid portrait of how diversity colors cultural philanthropy, and philanthropy more broadly, in the 21st century. Diversity and Philanthropy at African American Museums will be a valuable resource for scholars and practitioners engaged with African American heritage. It will also offer important insights for academics, as well as cultural administrators, nonprofit leaders, and fundraisers who are concerned with philanthropy and diversity.